Synthesis and Characterization of New Ionic Liquids for the Removal of Methylene Blue - MASSOUD , KERMANIORY ANI (2017)
Among the major classes of water pollutants, dyes have proven to be particularly problematic, both in terms of the quantity released to the environment and the difficulties faced in their recovery from aqueous solution. For this reason, there has been considerable interest in the development of means to remove dyes from aqueous waste streams.